Pyroptosis-Related Signatures for Predicting Prognosis in Breast Cancer - Ren, Tong; Guo, Xuhui; Zhang, Jingyang; Liu, Zhenzhen (Frontiers in Surgery, 2022)
ABSTRACT Background: Female breast cancer (BC) has become the most common cancer in the world, and its mortality was considerably higher in transitioning versus transitioned countries. Pyroptosis, an inflammation-dependent programmed cell death mediated by inflammasomes, has been observed in human colorectal tumors and gliomas. However, the characteristics of pyrolysis-related genes and their influence and mechanism on the tumorigenesis and progress of breast cancer were unknown. Methods: Based on the global public database, we used a comprehensive bioinformatics analysis to systematically analyze the expression of pyroptosis-related genes in breast cancer and their relationship in tumor progression. In addition, BC patients were divided into two groups, and the clinical features and outcomes could be better predicted by the consistent clustering of pyroptosis-related genes. Lasso Cox regression analysis was used to establish a risk score. Then, we further explored the prognostic value and clinical features of pyroptosis genes. Finally, we used the HPA platform to identify the expression at protein levels of the key genes. Results: We confirmed that the expression of pyroptosis-related genes was different in breast cancer and normal breast tissues. A high frequency of somatic mutations occured in BC. In addition, 33 pyroptosis-related proteins interacted frequently. Based on univariate analysis and the LASSO COX model, five pyroptosis-related genes (including GADMA, IL-6, NLRP6, CASP1, and CASP9), were obtained to calculate a risk score. The risk score was identified as an independent risk factor for the prognosis of breast cancer and might play an auxiliary role in clinical classification. The HPA platform confirmed that the expression trends of the key genes were consistent with our previous studies. Conclusion: Pyroptosis had an important effect on the progression of breast cancer. And the pyroptosis-related genes could be used as new prognostic biomarkers and therapeutic targets for breast cancer.